Mitigasi Pengelolaan Sampah di Kota Pariaman : Perspektif Teknis, Sosial, dan Institusional - Widiatmaja, Arya; Riyanto, Budi; Rosnani, Rosnani; Abadi, Kurniawan; Siska, Syafni Yelvi; Efrianto, Dody (Universitas Tanjungpura, 2026)
This study is motivated by the increasing volume of waste and the limited capacity for waste management in Pariaman City. It aims to (1) identify the main technical constraints in waste collection and processing in Pariaman; (2) assess public awareness and practices related to waste separation and disposal; (3) examine inter-agency coordination in supporting the implementation of waste-management policies. This is a qualitative case-study research and was conducted in Pariaman over ten months (February–November 2025). The informants were 4 persons selected through purposive sampling. Research instruments comprised semi-structured interview guides, observation checklists, and documentary evidence. Data were collected through in-depth interviews, participatory observation at the Tungkal Selatan landfill and related facilities, and document review. The findings indicate that, from a technical perspective, waste management in Pariaman falls into the “adequately compliant” category (mean score 75%). From a social perspective, public understanding of waste separation is relatively reasonable, classified as “compliant” (mean score: 81.5%). Institutionally, governance demonstrates adherence to standard operating procedures and coordination forums, which are also classified as “compliant” (mean score 82%). The study concludes that effective waste-management mitigation requires an integrated intervention comprising fleet renewal and scheduled maintenance, digitalization of operational systems, strengthening of technical capacity and community cadres, and clarification of authority alongside consistent inter-organization enforcement mechanisms. Recommendations are directed to Disperkim LH to develop an integrated operational plan, to the community to reinforce separation practices and participation in local waste banks, and to city policymakers to establish sustainable financing mechanisms, clarify institutional mandates, and implement more consistent enforcement procedures.